2016
DOI: 10.1590/0103-6440201600445
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Enamel and Dentin Surface Treatment on the Self-Adhesive Resin Cement Bond Strength

Abstract: The aim of this study was to evaluate the effect of enamel and dentin surface treatment on the micro-shear bond strength of self-adhesive cement. Seventy-two extracted third molars had their crowns embedded in acrylic resin and worn to obtain a flat enamel or dentin surface. The enamel and dentin specimens were randomly assigned to 8 groups (n=12) that were based on surface treatment (11.5% polyacrylic acid solution or no treatment), substrate condition (wet or dry) and storage period (1 day or 90 days), and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 21 publications
(55 reference statements)
0
10
0
7
Order By: Relevance
“…Thus, the degradation of the collagen fibre network is probably related to the lower bond strength values of the resin cement to root dentine observed in the irradiated teeth (Aggarwal , Rodrigues et al , Yamin et al ), as well as in the greater mismatch of the adhesive interface observed in SEM (Figs and ) (Gonçalves et al , Lieshout & Bots ), since the RelyX U200 resin cement bonding mechanism is promoted by acid monomers that, when interacting with the organic part of the resin cement and with the root dentine, demineralize and penetrate the dentine, creating micromechanical retention and chemical bonding to the hydroxyapatite. It does not depend on hybrid layer formation or presence of tags (Ferracane et al ), but rather of an ionization medium for the chemical reaction to occur (Mushashe et al ), which when altered by irradiation may have led to a lower number of chemical bonds between the cement and root dentine (Yamin et al ). These alterations, added to the stress caused by the endodontic instrumentation with reciprocating instruments and preparation of the post space (Versiani et al , Yamin et al ), may also justify the occurrence of fractures and microfractures in root dentine in irradiated teeth, verified in the SEM analysis (Figs and ), as well as the presence of cohesive failures in the dentine after the push‐out test (Naves et al , Gonçalves et al , Qing et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the degradation of the collagen fibre network is probably related to the lower bond strength values of the resin cement to root dentine observed in the irradiated teeth (Aggarwal , Rodrigues et al , Yamin et al ), as well as in the greater mismatch of the adhesive interface observed in SEM (Figs and ) (Gonçalves et al , Lieshout & Bots ), since the RelyX U200 resin cement bonding mechanism is promoted by acid monomers that, when interacting with the organic part of the resin cement and with the root dentine, demineralize and penetrate the dentine, creating micromechanical retention and chemical bonding to the hydroxyapatite. It does not depend on hybrid layer formation or presence of tags (Ferracane et al ), but rather of an ionization medium for the chemical reaction to occur (Mushashe et al ), which when altered by irradiation may have led to a lower number of chemical bonds between the cement and root dentine (Yamin et al ). These alterations, added to the stress caused by the endodontic instrumentation with reciprocating instruments and preparation of the post space (Versiani et al , Yamin et al ), may also justify the occurrence of fractures and microfractures in root dentine in irradiated teeth, verified in the SEM analysis (Figs and ), as well as the presence of cohesive failures in the dentine after the push‐out test (Naves et al , Gonçalves et al , Qing et al ).…”
Section: Discussionmentioning
confidence: 99%
“…The molars were used within three months of extraction. The root surface of each molar was embedded in Clássico acrylic resin (Clássico Dental Products, São Paulo, SP, Brazil) with the crown exposed (12).…”
Section: Restorative Proceduresmentioning
confidence: 99%
“…In addition, the self‐adhesive materials require means of ionization for the chemical reaction, which altered by irradiation may reinforce this hypothesis (Mushashe et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…In spite of its adhesion and polymerization mechanism, RelyX U200 resin cement had lower values of bond strength after radiotherapy, probably due to the reduction of calcium, phosphorus and carbon in the root dentine (De S a Ferreira et al 2016), which may generate fewer chemical bonds between cement and root dentine. In addition, the self-adhesive materials require means of ionization for the chemical reaction, which altered by irradiation may reinforce this hypothesis (Mushashe et al 2016).…”
Section: Discussionmentioning
confidence: 97%